Analysis Of The Socio-Economic Approximation Of Developmental Reforms, Strengthening Governance And Controlling Corruption In Mena -Panel Models – 1996-2022 - Boudali Bensekrane; Fahed Al-Duwailah (Journal of North African Economies, 2025)
The launch of sustainable development and welfare reforms requires the detection of obstacles, they have proven useless as a result of bureaucracy and corruption, despite the various natural, human and financial capitals of the South and the Third World that qualify them to confront poverty and unemployment, support local and international competitiveness, What necessitates reforming them by governing the performance, which indicated the importance of social indicators that refer to the characteristics of social construction; The network of relationships, values, trust, exchange, participation, communication and information, collected by the Social Progress Index (SCI) in this study, that aim to testing its impact on achieving well-being, in parallel with the governance index, through the application Panel models, on a sample of 21 countries in MENA region, during the period 1996-2022;The result study indicated the strength of the positive effect and the existence of a long-term relationship between them.